La censura como un acto de discriminación para la comunidad LGBTIQ+ y sus efectos en la identidad de las personas. Una aproximación desde la teoría de Judith Butler - Barquet Muñoz, José (2022)
Censorship is a form of discrimination as it is an act that seeks to make invisible or nullify the expression of people from the sexual diversity community. When facing censorship, people from the LGBTIQ+ community develop their own identity from a place of rejection or the unspoken. This article will show how from the earliest historical records to the present, people belonging to the sexual diversity community have been accompanied by manifestations of discrimination, including censorship. The relevance of identifying the impact that censorship has on the development of their own identity of the people's form the LGBTIQ+ collective will be exposed and explained from the theory of the American philosopher Judith Butler, for whom censorship is an act that reproduces and reinforces language that it is supposed to abolish. This analysis will exhibit different examples of discrimination and censorship to highlight the importance of identifying the types of censorship and discrimination that the LGBTIQ+ community faces and how it impacts on the development of their own identity.